PARTISIPASI HUKUM DAN POLITIK MASYARAKAT DESA GALUMPIT DALAM MEMAHAMI URGENSI HAK MILIK ATAS TANAH MELALUI PEMANFAATAN LKBH UNIKOM - Situmeang, Sahat Maruli Tua (Indonesian Community Service and Empowerment Journal (IComSE), 2025)
The activities of human life are increasing and everything is done on the ground. Many cases of disputes occur due to lack of legal and political participation. This is as happened in Galumpit Village where there are still many people who do not have proof of ownership of land rights and the low level of community knowledge in the contract or agreement process, both for land sale and purchase agreements and other objects sale and purchase. In an effort to implement the tri dharma of UNIKOM FH higher education, UNIKOM LKBH, International Women University Political Science Study Program in collaboration with Galumpit Village in realizing legal and political participation in order to increase legal awareness of the Galumpit Village community. Based on the results of these service activities, it shows that in an effort to optimize the registration of property rights to land in Galumpit Village, synergy between stakeholders is needed such as the legal structure in this case the government, BPN, and village apparatus, legal substance, namely related regulations, as well as the participation of the relevant community as a system by optimizing information technology in realizing accurate and responsive data and processes, so as to achieve a just society. Keywords :Legal and political participation, land ownership rights, LKBH UNIKOM